Evaluation of State Cryptographic Institutions - Adi Sulistyo; Yono Reksoprodjo (The Republic of Indonesia Defense University, 2015)
State cryptographic institutions, coordinated by the State Cryptography Agency have contribute to protect the state classified information from potential threats and vulnerabilities posed by information warfare, using the methods of cryptography. State Cryptography Agency, so that need the anticipatory efforts to reduce the inhibiting factors. The research was conducted using the qualitative research methods with descriptive analysis techniques. Based on this research, it is known that the role of State Cryptography Agency in facing the information warfare is more widely available in the defense/defensive effort to protect state information, as well as there are still some factors that cannot be minimized.